Anterior chest wall pilonidal sinus: disease at a rare site - Niaz Soomro; Hira Pervez (Journal of the Pakistan Medical Association, 2021)
Pilonidal sinus is defined as an infected tract in the skin, commonly containing a tuft of hair. The most common locations are buttocks, axillae, groin, etc., but it can also develop at rare locations. We present a case of a 24-year-old, hirsute male with recurrent infected discharging sinus on the anterior chest wall, at a tertiary care hospital in Karachi. The patient had earlier undergone incision and drainage multiple times before he finally came to us. On evaluation and exploration a sinus tract containing a tuft of hair was excised from the anterior chest wall. A pilonidal sinus can develop in any area containing hair under friction. Hence, it should be included under the differential diagnosis of any long-standing sinus over a hairy area. Keywords: chest wall sinus, anterior chest wall, Continuous....